MOVING AVERAGE AS A METHOD OF FORECASTING GLASS INVENTORY ANALYSIS (CASE STUDY: TOP SENYUM STORE) - natasya leuwol (Electro Luceat, 2021)
In inventory, TOP SMILE employees must carry out inventory checks by checking items one by one and then recording. The problem that arises is that the employee on duty has difficulty estimating the number of needs that must be ordered from each type of item. One of the goods with the most market demand is glass. In the supply of glassware, sometimes employees have difficulty in estimating how much is needed. This will have an unfavorable impact, when the goods requested do not match the needs or are excessive. Based on the existing problems, the author wrote a study with the title Moving Average as a Glass Glass Inventory Forecasting Analysis Method at TOP SMILE. The results of the inventory forecasting calculation for May 2021 using the Moving Average method are 6 for glass goods. Then after the results of the inventory forecasting calculations are obtained, it is continued with the calculation of the MAPE value as a test of the accuracy of the previously obtained forecasting value. In the results of the research conducted, it can be concluded that the MAPE value of 47.095% indicates that the forecasting results obtained are quite accurate. With the inventory forecasting analysis carried out in this study, it can help facilitate the owner's service process in providing goods for the future.